Echocardiographically Measured Epicardial Fat Predicts New-onset Atrial Fibrillation after Cardiac Surgery - Gunturk,Ertugrul Emre (2020)
Abstract Objective: The current study aims to investigate the role of echocardiographically measured epicardial adipose tissue (EAT) thickness in the prediction of new-onset atrial fibrillation (AF) following coronary artery bypass grafting (CABG) surgery. Methods: One hundred and twenty-four patients scheduled to undergo isolated on-pump CABG due to coronary artery disease were enrolled to the current study. Patient characteristics, medical history and perioperative variables were prospectively collected. EAT thickness was measured using transthoracic echocardiography (TTE). Any documented episode of new-onset postoperative AF (POAF) until discharge was defined as the study endpoint. Fortyfour participants with POAF served as AF group and 80 patients without AF served as Non-AF group. Results: Two groups were similar in terms of baseline echocardiographic and laboratory findings. In laboratory findings, the groups were similar in terms of the studied parameters, except N-terminal pro-brain natriuretic peptide (NT Pro-BNP), which was higher in AF group than in Non-AF group (P=0.035). The number of left internal mammary artery (LIMA) grafts was not different in both groups. AF group had higher cross-clamp (CC) and cardiopulmonary bypass (CPB) times than Non-AF group (P=0.01 and P<0.001). In multivariate logistic regression analysis, EAT was found an independent predictor for the development of POAF (OR 4.47, 95% CI 3.07-5.87, P=0.001). Conclusion: We have shown that EAT thickness is associated with increased risk of AF development and can be used as a prognostic marker for this purpose.